Plant-based production of a protective vaccine antigen against the bovine parasitic nematode Ostertagia ostertagi - Laurens Zwanenburg; Jimmy Borloo; Bregt Decorte; Myrna J. M. Bunte; Sanaz Mokhtari; Sonia Serna; Niels-C. Reichardt; Leen J. M. Seys; Angela van Diepen; Arjen Schots; Ruud H. P. Wilbers; Cornelis H. Hokke; et al. (Scientific Reports, 2023)
Abstract The development of effective recombinant vaccines against parasitic nematodes has been challenging and so far mostly unsuccessful. This has also been the case for Ostertagia ostertagi, an economically important abomasal nematode in cattle, applying recombinant versions of the protective native activation-associated secreted proteins (ASP). To gain insight in key elements required to trigger a protective immune response, the protein structure and N-glycosylation of the native ASP and a non-protective Pichia pastoris recombinant ASP were compared. Both antigens had a highly comparable protein structure, but different N-glycan composition. After mimicking the native ASP N-glycosylation via the expression in Nicotiana benthamiana plants, immunisation of calves with these plant-produced recombinants resulted in a significant reduction of 39% in parasite egg output, comparable to the protective efficacy of the native antigen. This study provides a valuable workflow for the development of recombinant vaccines against other parasitic nematodes.